Evaluasi Kualitas Layanan (QoS) pada Jaringan Wi-Fi 6 Dibandingkan dengan Wi-Fi 5 - Fauzan Prasetyo Eka Putra; Ekawati Ekawati; Akhmad Vidyan; Moh. Ali (Jurnal Informatika Dan Tekonologi Komputer (JITEK), 2025)
The increasing demand for reliable and efficient wireless connectivity, especially for real-time applications such as video conferencing, online gaming, and VoIP services, is driving the adoption of more advanced networking technologies. This study aims to evaluate and compare the quality of service (QoS) between two generations of Wi-Fi standards, namely Wi-Fi 6 (IEEE 802.11ax) and Wi-Fi 5 (IEEE 802.11ac), based on key performance parameters such as throughput, latency, jitter, and packet loss. Tests were conducted in controlled laboratory scenarios and dense user environments to simulate real-world conditions. The measurement results show that Wi-Fi 6 is able to provide significant improvements in terms of spectrum efficiency, traffic management, and resilience to interference, thanks to superior features such as OFDMA, MU-MIMO, BSS Coloring, and Target Wake Time (TWT). Compared to Wi-Fi 5, Wi-Fi 6 shows more stable and responsive performance, making it a more suitable solution for modern network needs with high traffic loads and low latency demands. These findings reinforce the potential of Wi-Fi 6 as a superior standard in supporting QoS in various intensive usage scenarios.